HIPOTIROID KONGENITAL: DIAGNOSIS, MANIFESTASI KLINIS, DAN PENATALAKSANAAN - Latifah Mukhlisatunnafsi (Yayasan Pendidikan Medika Indonesia, 2024)
Congenital hypothyroidism is a lack of thyroid hormone production in newborns due to anatomic abnormalities of the thyroid gland, metabolic disorders for thyroid hormone formation, and iodine deficiency. The global incidence of congenital hypothyroidism is 1:2000 to 1:3000. In Indonesia, screening for congenital hypothyroidism has not been carried out nationally, only in a number of areas. Of the 14 provinces in Indonesia, a temporary incidence of 1:2513 was obtained. It is known that 95% of congenital hypothyroidism does not show typical clinical signs and symptoms at birth, so it is necessary to carry out early screening as a step in establishing the diagnosis. Management carried out as recommended by IDAI is by administering L-T4 (levothyroxine) which is given as soon as possible after the diagnosis is established and the best therapy begins before the baby is 14 days old.